2016
DOI: 10.21273/horttech.26.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of Bahiagrass Roots Treated with Micronutrients, Rare Earth Elements, and Plant Hormones

Abstract: Bahiagrass (Paspalum notatum) is widely used for slope protection and water and soil conservation in southern China. The plants develop an extensive root system that plays a crucial role in the protection of both soil and water. However, little is currently known about the factors that influence early root growth in bahiagrass. Here, the effects of boron (B), calcium (Ca), iron (Fe), lanthanum (La), cerium (Ce), salicylic acid (SA), and melatonin (MLT) on root growth characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…We have previously discovered that La could promote root growth in bahiagrass [10]. In this study, we found that La could also increase root activity.…”
Section: Effect Of La On the Root Activity And Cell Wall Polysaccharide Content Of Rootssupporting
confidence: 50%
See 2 more Smart Citations
“…We have previously discovered that La could promote root growth in bahiagrass [10]. In this study, we found that La could also increase root activity.…”
Section: Effect Of La On the Root Activity And Cell Wall Polysaccharide Content Of Rootssupporting
confidence: 50%
“…Bahiagrass (Paspalum notatum) is widely used for slope protection and soil and water conservation in southern China owing to its extensive and deep root system. Our preliminary work has shown that La could significantly improve bahiagrass root growth [10]. It has been reported that La absorbed by plant roots is mainly attached to the cell wall of root cells and that La alleviates the toxic effects of aluminum by changing the porosity of the cell wall [11].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Calcium in the soil, according to Liu et al, [42] and Liu et al, [43]; helps in the proper functioning of the root tips of growing plants and maintaining the strength of the various plant cell walls. Calcium present in fish pond wastewater ranged between 19.34 and 24.20 mg/L while that of the boreholes used to provide water to the various ponds ranges between 26.26 and 32.30 mg/L and that of the river water was 31.03 mg/L.…”
Section: Calcium (Ca)mentioning
confidence: 99%